2012
DOI: 10.1186/1471-2458-12-901
|View full text |Cite
|
Sign up to set email alerts
|

Possible relation between maternal consumption of added sugar and sugar-sweetened beverages and birth weight – time trends in a population

Abstract: BackgroundHigh birth weight (BW) is a risk factor for later obesity. In Norway, mean BW and proportion of large newborns increased from 1989 to 2000 and subsequently decreased to the 1989 level by 2010. The purpose of the study was to explore causes of this temporary increase.MethodsFrom a regional prospective database pregnancy and newborn data were extracted for all 33088 singleton pregnancies resulting in live infants born at term without malformations during 1989–2010. Trends in BW, ponderal index and prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 44 publications
3
16
0
Order By: Relevance
“…We have previously shown that temporary increases in mean BW and HBW babies in Norway occurred in parallel to a marked increase and subsequent decrease in national consumption of SSC, and we suggested a causal relationship (Grundt et al, 2012). This study may seem to contradict that hypothesis, but it may still be true.…”
Section: Discussionsupporting
confidence: 51%
See 4 more Smart Citations
“…We have previously shown that temporary increases in mean BW and HBW babies in Norway occurred in parallel to a marked increase and subsequent decrease in national consumption of SSC, and we suggested a causal relationship (Grundt et al, 2012). This study may seem to contradict that hypothesis, but it may still be true.…”
Section: Discussionsupporting
confidence: 51%
“…In this study, fewer participants had pre‐pregnancy diabetes or were diagnosed with GDM than both nonparticipants and the participants in our previous cohort study where data were available for all pregnant women within a region (Grundt et al, 2012, Nilsen et al, 2009). As SSC consumption decreased and leisure time exercise increased in Norway during the recruitment period to the MoBa study (Grundt et al, 2012), glucose tolerance among pregnant women was probably generally better. Furthermore, women with increased cardio‐metabolic risk factors, such as obesity, reduced glucose tolerance, or GDM, may have been early adopters of the trend to reduce intakes of SSC.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations